Identifikasi Daerah Rawan Longsor Berdasarkan Kecepatan Gelombang Geser (Vs30) Di Desa Salamkanci, Kecamatan Bandongan - Ilqima Rahma; Dian Susri Nurhaci (Stasiun Geofisika Kelas I Sleman, 2023)
Bandongan District is one of the sub-districts in Magelang Regency which has a detailed area of 45.79 km2 which has a fairly high history of landslides. This research aims to identify landslide-prone areas based on microseismic parameters using microtremor measurement data by BMKG Class I Sleman Yogyakarta. Microtremor analysis was carried out using the HVSR method with the help of Geopsy software. The H/V curve inversion was carried out using the dinver program to obtain a ground profile containing the depth of each layer relative to the shear wave velocity value. The research results show that the range of dominant frequency values is relatively varied and is in the range between 1.01502 - 17.6748 Hz. The amplification value is in the range between 2.64533 - 23.5064 with a large distribution of dominantly high amplification factors. The value of shear wave velocity up to a depth of 30 meters (Vs30) in this area is classified as moderately dominant with a range of 209.16 – 876.90 m/s which is included in the classification of solid soil and soft rock in the form of clay and breccia. This area has varying sediment thickness but is dominated by thick sediment with a range of 3.86 – 232 meters. The area in Bandongan District, Magelang Regency which has the highest level of vulnerability to landslides is found at measurement point number 19 with a high risk of damage.